(untitled) (Nexo Revista Científica, 2021)
Authors carried out the QMW analysis, on four crater Alchichica (ALCHI), Atexcac (ATx), La Preciosa (LPr) and Quechulac (QUE), with monthly frequency during one year. Protocols were used to evaluate total coliforms (TC), fecal coliforms (FC), enterococcus (ENT), E. coli, (E. coli + Rodococcus) and Clostridium perfringers. The presence of E. coli was detected in all the studied lakes, and the most contaminated was QUE, followed by ALCHI y LPr. The pH, DO and the temperature no recorded variation. The salinity registered fluctuations 0 a 10.0 mgL-1. ATx, LPr and ALCHI recorded contamination derived from goats, while QUE registered fecal contamination from human source. The presence of E. coli is variable in Axalapascos, because of that is allochthones to the system and opportunistic due to the surrounding cattle fecal discharge associated to unwell agricultural practice. The levels of microbiological contamination in the crater lakes, exceeding regulations for the human, agricultural and tourism.